Antihyperglycaemic potential of rosmarinic acid attenuates glycoprotein moiety in high-fat diet and streptozotocin-induced diabetic rats. Issue 1 (1st January 2020) - Ramalingam, Sundaram; Karuppiah, Muthu; Thiruppathi, Muthusamy
Abstract : Rosmarinic acid is a polyphenolic phytoconstituent isolated from the leaves of Plectranthus amboinicus and its structure was established by analysis of its 1 H, 13 C and HRMS. The effect of rosmarinic acid was evaluated by deranged plasma and tissues glycoprotein components in diabetic rats. Rosmarinic acid was administered to diabetic rats for 30 days significantly declined the levels of blood glucose and glycosylated haemoglobin with elevation of plasma insulin and haemoglobin levels. Rosmarinic acid administration improved the glycogen content in liver and muscle tissue by reinstating the altered glycogen metabolic enzymes such as glycogen synthase and glycogen phosphorylase. Further, the altered levels of plasma and tissue glycoprotein components were restored to near normal upon treatment with rosmarinic acid. In addition, rosmarinic acid treatment prevented body weight loss and excessive intake of food and water. The effect produced by the rosmarinic acid on various parameters was comparable to that of metformin.